Treatment practices and costs among patients with psoriatic arthritis: A Japanese hospital claims database analysis. Issue 6 (2nd November 2021) - Inui, Kentaro; Sato, Masayo; Esterberg, Elizabeth; Parikh, Rohan C.; Kimura, Shuichi; Torisu-Itakura, Hitoe
Abstract: Objective: Assess patient characteristics, real-world treatment patterns, and health care resource utilization (HCRU) among patients with psoriatic arthritis (PsA) in Japan. Methods: Patients diagnosed with PsA from April 2009 through July 2017 were identified from the Medical Data Vision database. Patient characteristics, treatment patterns, and HCRU were evaluated for these patients. Results: A total of 639 patients met inclusion criteria and were included in the analysis for patients with a PsA diagnosis. Over 12 months following diagnosis, patients received oral NSAIDs (61.7%), conventional synthetic disease-modifying antirheumatic drugs (DMARDs) (55.1%), corticosteroids (35.1%), topical NSAIDs (34.0%), adalimumab (14.7%), infliximab (9.7%), secukinumab (5.0%), ustekinumab (4.5%), ixekizumab (1.6%), and golimumab (1.6%). A total of 227 (35.5%) patients initiated biologic DMARDs (bDMARDs) over the median 25.2 months of study follow-up. Compared with the overall group of patients diagnosed with PsA, patients who initiated bDMARDs had higher median total per-patient health care costs (27, 772 vs. 11, 316), lower median per-patient hospitalization costs (31, 164 vs. 39, 359), and fewer median hospital days per admission (8.0 vs. 12.0 days). Conclusion: This study presents knowledge of the current state of patient characteristics, treatment patterns, HCRU, and costs among patients with PsA in Japan. Considering the relatively recent guideline recommendations, the preliminary treatment patterns suggest physicians may be following treatment guidelines.